ANALISIS TATANIAGA TANDAN BUAH SEGAR KELAPA SAWIT DI DESA TEMPAKAN KECAMATAN BATU ENGAU KABUPATEN PASER (Marketing Analysis of Fresh Fruit Bunches of Oil Palm in Tempakan Village, Batu Engau Subregency, Paser Regency) - SIMON SUTRADO SIMANJUNTAK; ACHMAD ZAINI (Universitas Mulawarman (University of Mulawarman), 2019)
The purposes of this study were to know marketing channel, marketing margin, share, and marketing profit of fresh fruit bunches of oil palm in Tempakan Village, Batu Engau Subregency, Paser Regency. The study was conducted from June to August 2016. The sampling method was done with two ways as random sampling in farmer level and in marketing channel as snowball sampling. Data analysis were done by calculating marketing margin, share, and marketing profit. The results of this study showed that there are two marketing channels in reserach location are channel of level zero and channel of level one. Marketing margin in farmer level was Rp40.39 kg-1 and margin in whole trader level was Rp314.44 kg-1. The average share of farmer level was 97.58% and in trader level was 81.48%. Margin and share that profitable for farmer is at channel of level zero. The average of profit in whole trader level of fresh fruit bunches was 112.75%, that meant marketing by whole trader is profitable.